The Slametan Tradition as Local Wisdom in Contextual Learning in Schools: A Literature Review - Addy Septyawan; Ani Rakhmawati (Journal of Science and Education (JSE), 2026)
This study aims to analyze the integration of the slametan tradition as local wisdom in contextual learning through a literature review of 20 relevant articles. The study was conducted using the systematic literature review method which involves the process of identification, selection, and thematic analysis of articles that contain the development of teaching materials, local cultural integration, and innovative learning approaches. The results of the synthesis show that most of the studies apply ADDIE development and research and development models, as well as utilize the local cultural context as a reinforcement of learning meaning. The integration of cultural values, including the slametan tradition, has been proven to be able to improve concept understanding, cultural literacy, and student learning engagement through learning experiences that are closer to social reality. Previous research also confirms that local wisdom makes a significant contribution to character building, appreciation for diversity, and strengthening cultural identity. However, there is still a research gap related to the systematic use of local traditions in contextual learning in schools. These findings show that the integration of local wisdom needs to be formulated in the form of teaching materials or a more structured learning model. Overall, this study emphasizes the importance of using local culture, especially the slamutan tradition, to enrich the learning context and increase the relevance of the material for students.